SCIDOT-29. EVALUATING THE FEASIBILITY OF INTRANASAL FLT DELIVERY FOR PET IMAGING OF PRIMARY BRAIN TUMORS. (11th November 2019) - Carlisle, Grant; Fowler, Austin; Soma, Joel; Drewes, Lester; Friday, Bret
Abstract: INTRODUCTION: Glioblastoma (GBM) is an aggressive primary brain tumor with a dismal prognosis. Overall survival rates have been correlated to initial tumor resection making improved imaging techniques necessary for improved patient outcomes. Functional imaging with fluorothymidine (FLT) has been limited due to inefficient transfer through the blood-brain-barrier. In this experiment, we strived to test the efficacy of tritium-labeled-FLT ( 3 H-FLT) delivery to brain tissue through intranasal (IN) versus intravenous (IV) administration in a rat model. METHODS: Adult rats ( Sprague Dawley, 180-200g ) received 3 H-FLT through either an IN or IV delivery method. At 5, 20, and 60 minutes, concentrations of 3 H-FLT were measured in 16 brain regions as well as blood and non-target organs via isotope quantitation using scintillation detection. Pharmacokinetic parameters were calculated. RESULTS: Intranasal olfactory bulb concentrations of 3 H-FLT trended higher compared to IV olfactory bulb. All other brain region concentrations were insignificantly different. Kp (brain-blood ratio) values mimicked this trend. Secondary calculations were performed to evaluate intranasal CNS drug targeting. Initial trends showed a more effective IN drug penetration to the olfactory bulb, spinal cord, and hippocampus. Drug targeting efficiency (DTE%) was found to be highest in the olfactory bulb at 212%, but all other brain regions were greater than 100% suggesting more efficient drug targeting with intranasal administration. Nose-to-brain direct transport percentage (DTP%), and comparative brain bioavailability (B%) showed similar trends. Non-target tissues including heart, lung, adipose and skeletal muscle were collected in the 5- and 60-minute trials and found to be significantly higher than all brain concentrations. CONCLUSION: Drug delivery calculations suggest increased efficacy with IN administration of FLT to all brain regions compared to IV administration. However, additional optimization is likely necessary to improve PET imaging of primary brain tumors using IN delivery due to the relatively small differences observed.